RESEARCH TRENDS COMPUTATIONAL-ETHNOPEDOLOGY IN ELEMENTARY SCHOOL SCIENCE LEARNING: BIBLIOMETRIC ANALYSIS AND FIELD NEEDS EXPLORATION - Ibrahim Ibrahim; Muhammad Erfan; Mohammad Archi Maulyda; Nurkhaerat Alimuddin (BIOCHEPHY: Journal of Science Education, 2025)
This study aims to identify the current state of elementary school students' critical and creative thinking skills in science learning and to explore the need for technology-based learning media and local wisdom as a basis for developing interactive e-modules based on computational ethnopedology. The study used a mixed-methods exploratory method through observation, questionnaires, and interviews and was supplemented by bibliometric analysis of global publications related to computational thinking, HOTS, and culture-based learning. Observational data showed that students' critical and creative thinking skills were still low, with scores of 54.5 and 58.2, respectively, in line with interview findings that learning was still dominated by lectures and textual materials. The questionnaire results showed that 87% of students needed visual teaching materials in the form of animation, while 90% of teachers considered the importance of integrating local wisdom in science learning. Bibliometric analysis showed a significant increase in computational thinking research from 2020 to 2022, but integration with local wisdom was still limited. These findings confirm the gap between learning needs in the field and global research trends. Therefore, the development of interactive e-modules based on computational ethnopedology has the potential to be a relevant innovation to support the development of critical and creative thinking skills in elementary school students. This research provides an empirical and theoretical foundation for the development of culture- and technology-based learning media in subsequent research phases.